1991
DOI: 10.1007/bf02990347
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency, ethanol, and myocardial ischemia affect lipoperoxidation in rats

Abstract: The production of oxygen free radicals can be stimulated by excess iron, cadmium, nickel, and the like. Inversely, copper, zinc, and selenium inhibit production, either via their own action or via antiradical metalloenzymes. The study involved determining the effect of zinc deficiency combined with chronic ethanol administration on the status of blood and tissue free radicals, as well as on cardiac function in isolated, perfused rats' hearts. Animals were fed a basic diet containing residual zinc at 0.2-0.3 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Animal studies have shown more compelling evidence of ROS-induced damage whereby chronic alcohol consumption causes an increase in cardiac lipid peroxidation, the effects of which are more severe in animals with concomitant zinc deficiency (53,54). Evidence to support some element of a free-radical mediated event in the cause of AHMD has been obtained in studies showing that, in alcohol-treated rats, the shift in fatty acid profile was inhibited by dietary alpha-tocopherol (55).…”
Section: The Involvement Of Free Radical Mediated Damagementioning
confidence: 99%
“…Animal studies have shown more compelling evidence of ROS-induced damage whereby chronic alcohol consumption causes an increase in cardiac lipid peroxidation, the effects of which are more severe in animals with concomitant zinc deficiency (53,54). Evidence to support some element of a free-radical mediated event in the cause of AHMD has been obtained in studies showing that, in alcohol-treated rats, the shift in fatty acid profile was inhibited by dietary alpha-tocopherol (55).…”
Section: The Involvement Of Free Radical Mediated Damagementioning
confidence: 99%
“…[7][8][9] Excess metals like iron, nickel and cadmium stimulate the production of free radicals. 10 Among all factors, cigarette smoking is a major source of oxidant stress, which alters antioxidant ability and antioxidant resistance. 11 It should be noted that plasma peroxide, free radical, and antioxidant levels may vary with age.…”
mentioning
confidence: 99%
“…It has been suggested that the pathogenic mechanisms responsible for these alterations involve ROS-induced cell injury (49). In fact, ROS and free radicals are generated during ethanol metabolism, causing oxidative stress and lipid peroxidation in cardiac tissue (10), as well as in many other organs, such as liver, brain, and skeletal muscle (36,49). Furthermore, ethanol metabolism-induced oxidative stress also causes oxidative degradation of the mitochondrial genome (36).…”
Section: Cardioprotection and Redox Balancementioning
confidence: 98%